Guest

pl give the answer with steps, see the following attachment. thanks

pl give the answer with steps, see the following attachment. 
thanks 

Question Image
Grade:9

2 Answers

Arun
25758 Points
3 years ago
Dear student
 
take LCM
 
hence you will get
 
( 5 + 1 – 2 sqt 5 + 5 + 1 + 2 sqrt 5) / (5-1)
 
 = 12 /4 = 3
 
hence a = 3 and b = 0
Piyush Kumar Behera
436 Points
3 years ago
As the previous solution was not illustrated properly,Hence here is a better solution..
\frac{\sqrt{5}-1}{\sqrt{5}+1}+\frac{\sqrt{5}+1}{\sqrt{5}-1}
Taking LCM of the above expression we get
=\frac{(\sqrt{5}-1)^{2}+(\sqrt{5}+1)^{2}}{(\sqrt{5}-1)(\sqrt{5}+1)}
= \frac{5+1-2\sqrt{5}+5+1+2\sqrt{5}}{\sqrt{5}^{2}-1^{2}}
=\frac{12}{5-1}
 
a  = 12/4 = 3
b = 0
 
 
So the answer is a = 3 and  b = 0.
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free